Hidup dalam Kasih Karunia Allah: Masa Lalu versus Masa Sekarang (Efesus 2:1-10) - Sihombing, Warseto Freddy; Berutu, Icca; Gaol, Ester Novita Lumban; Hulu, Betty Putri Irene (Institut Agama Kristen Negeri Manado, 2023)
In this article, Paul explains and summarizes the general condition of mankind, the goodness of God, and the nature of salvation that God has provided for sinners (lost) through Jesus Christ. Through the hermeneutical-analysis method, the author explains the truth about the existence of humans who have died because of sin and cannot do anything so that God's grace is needed to bring the dead humans to life. This is a picture of life outside of Christ (past) and life in Christ (present).